Resolvin D1 attenuates the inflammatory process in mouse model of LPS‐induced keratitis. Issue 21 (15th October 2020) - Petrillo, Francesco; Trotta, Maria Consiglia; Bucolo, Claudio; Hermenean, Anca; Petrillo, Arianna; Maisto, Rosa; Pieretti, Gorizio; Pietropaolo, Michela; Ferraraccio, Franca; Gagliano, Caterina; Galdiero, Marilena; D'Amico, Michele
Abstract: The aim of this study was to investigate the effects of the lipid mediator Resolvin D1 in experimental keratitis. C57BL/6J mice were injected with lipopolysaccharide (2 µg/eye), and after 24 hours, the corneal damage was assessed. Clinical score was quantified, and corneal inflammatory biomarkers were detected by immunohistochemistry. A robust accumulation of sub‐epithelial macrophages and polymorphonuclear leucocytes, chemokine (C‐X‐C motif) ligand 1 (also known as keratinocyte‐derived chemokine), interleukin‐10 and promoters of apoptosis was also observed in lipopolysaccharide‐treated mice. Formyl peptide receptor 2 corneal expression was also assessed. The corneal stroma treated with lipopolysaccharide was characterized by presence of macrophages of M1‐like subtype and immature fibroblastic cells, marked with Ki67, not fully differentiated in fibroblasts. Indeed, the staining of the cornea with anti‐vimentin antibodies, a marker of differentiated myofibroblasts, was very faint. Resolvin D1 attenuated all the inflammatory parameters assessed in the present study, except for IL‐10. In conclusion, the data presented here seem to be consistent with the hypothesis that Resolvin D1 protected the cornea from the lipopolysaccharide‐induced keratitis by acting on several inflammatory components of this damage, pivoted by Formyl peptide receptor 2 (FPR2) activation and macrophages‐leucocytes activity.